Protein enrichment of coconut sapal (Cocos nucifera) using solid substrate fermentation - Laviste, Ma. Carmencita Navarro; De Leon, Sonia Y. (1989.)
Proximate composition of the raw material, coconut residue or "sapal", comparative study of the test organisms namely Trichoderma viride and Aspergillus niger, and the determination of their appropriate nutrient supplementation were undertaken in the study. The sapal examined had a pH of 6.52% and contained the following moisture, 41.10%; ash, 0.86%; crude fiber, 31.18%; crude fat, 19.89%, crude protein, 3.87%; and CHO (by difference), 3.01%. The optimum nutrient levels and fermentation time of the test organisms revealed that T. viride gave appreciable outcomes from samples containing C:N ratios of 90:1 and 130:1 during the 6th day of fermentation while A.niger manifested favorable results from sample 170:! on the 3rd day. Data revealed that during the 6th fermentation day, sample 90:1 with the growth of T. viride received these following attributes: physical appearance, green with light creamy yellow; pH, 3.55; and protein, 13.72%. Sample 130:1 having the same fungi growth and day of analysis showed a green with creamy light yellow in appearance, pH value of 3.6, and 12.91% protein. Growth of A. niger in sample 170:1 during the 3rd day resulted to an appearance of grey or greyish black, pH value of 4.95, and protein content of 8.57%.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products; Fermentation